2022
DOI: 10.1097/upj.0000000000000269
|View full text |Cite
|
Sign up to set email alerts
|

Urology Practice Acquisitions by Private Equity Firms from 2011–2021

Abstract: Introduction: Private equity firms have recently acquired several large urology practices in the United States. As little is known about these acquisitions, we sought to characterize trends in urology practice consolidation. Methods:We compiled urology practice acquisition data via financial databases, news outlets, practice websites, and Internet keyword search for the time period January 1, 2011 through March 15, 2021. For each acquisition, we determined the acquiring group, number of employed urologists, pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 17 publications
0
23
0
Order By: Relevance
“…In the beginning, private equity firms acquired larger urology practices (mean of 61 urologists) with ownership of ancillary services. Later, private equity firms consolidated through acquisitions of smaller practices (mean of 16 urologists) [37 ▪▪ ]. Nie et al [37 ▪▪ ] estimate about 7.2% of urologists work for private equity-backed firms.…”
Section: Medical Specialtiesmentioning
confidence: 99%
See 1 more Smart Citation
“…In the beginning, private equity firms acquired larger urology practices (mean of 61 urologists) with ownership of ancillary services. Later, private equity firms consolidated through acquisitions of smaller practices (mean of 16 urologists) [37 ▪▪ ]. Nie et al [37 ▪▪ ] estimate about 7.2% of urologists work for private equity-backed firms.…”
Section: Medical Specialtiesmentioning
confidence: 99%
“…Later, private equity firms consolidated through acquisitions of smaller practices (mean of 16 urologists) [37 ▪▪ ]. Nie et al [37 ▪▪ ] estimate about 7.2% of urologists work for private equity-backed firms. Over 25% of all urologists practicing in New Jersey and Maryland are employed by private equity platforms [37 ▪▪ ].…”
Section: Medical Specialtiesmentioning
confidence: 99%
“…Private equity (PE) investment is a major driving force in healthcare today, offering consolidation and the ability to scale up independent practices to compete in a dynamic market. For example, one recent study found that in Maryland and New Jersey, more than 25% of urologists were employed by a private equity backed platform company[1]. However, recent trend of private equity (PE) backed consolidation in ophthalmology and the healthcare system as a whole continues to raise concerns regarding patient care, physician autonomy, and overall health system costs[2, 3].…”
Section: Introductionmentioning
confidence: 99%
“…1 PE acquisition continues to play a greater role in healthcare in the United States, particularly affecting procedure-based, outpatient-heavy fields such as dermatology, urology and ophthalmology. 2-4…”
Section: Introductionmentioning
confidence: 99%
“…1 PE acquisition continues to play a greater role in healthcare in the United States, particularly affecting procedure-based, outpatient-heavy fields such as dermatology, urology and ophthalmology. [2][3][4] PE investment has implications not only on practice management strategy, but also the long-term economic wellbeing of practices. PE buyouts often involve raising substantial amounts of debt, often 70 to 80 percent of the purchase price, to meet the cost of acquisition.…”
Section: Introductionmentioning
confidence: 99%